Trade and the legal entity identifier. - Beck, Steven (Metro Manila, Philippines Asian Development Bank, 2019)
The LEI is designed for legal entities, including financial institutions, major corporations, governments, and small and medium sized enterprises. For instance, banks with an LEI provide more certainty in customer onboarding credit approval and transaction processes. The brief outlines the advantages of implementing the LEI and how its adoption could transform business processes, particularly in supporting the inclusion of small and medium sized enterprises in the global economy.
Keywords: Public administration; Electronic books